2019
DOI: 10.1038/s41467-019-11243-4
|View full text |Cite
|
Sign up to set email alerts
|

Determining the rotation direction in pulsars

Abstract: Pulsars are rotating neutron stars emitting lighthouse-like beams. Owing to their unique properties, pulsars are a unique astrophysical tool to test general relativity, inform on matter in extreme conditions, and probe galactic magnetic fields. Understanding pulsar physics and emission mechanisms is critical to these applications. Here we show that mechanical-optical rotation in the pulsar magnetosphere affects polarisation in a way which is indiscernible from Faraday rotation in the interstellar medium for ty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…The wave transverse phase structure is hence rotated as the wave propagates along the rotation and magnetic axis . Comparing now (4.17) with the phase shift introduced by rotation between circularly polarised eigenmodes (Gueroult et al 2019 a , 2020), that is to say to the SAM mechanical Faraday effect, one finds that the phase shifts are in both cases proportional to the ratio of plasma angular frequency to wave angular frequency , but that in addition, (4.17) depends linearly on the azimuthal wavenumber . This scaling is also consistent with image rotation in an isotropic dielectric (Götte et al 2007).…”
Section: Faraday–fresnel Rotation For Tg Wavesmentioning
confidence: 85%
See 2 more Smart Citations
“…The wave transverse phase structure is hence rotated as the wave propagates along the rotation and magnetic axis . Comparing now (4.17) with the phase shift introduced by rotation between circularly polarised eigenmodes (Gueroult et al 2019 a , 2020), that is to say to the SAM mechanical Faraday effect, one finds that the phase shifts are in both cases proportional to the ratio of plasma angular frequency to wave angular frequency , but that in addition, (4.17) depends linearly on the azimuthal wavenumber . This scaling is also consistent with image rotation in an isotropic dielectric (Götte et al 2007).…”
Section: Faraday–fresnel Rotation For Tg Wavesmentioning
confidence: 85%
“…Asking this question is fundamentally asking for physical probes sensitive to fluid vorticity. Interestingly, it has recently been shown that rotation could imprint its signature on the polarisation of a wave propagating through a rotating plasma (Gueroult et al 2019 a ), offering in turn unique opportunities to infer the rotation direction in pulsars. A challenge here, however, is that in a magnetised plasma both this polarisation drag effect (Jones 1976; Player 1976) (also referred to as the mechanical Faraday effect) and the classic Faraday rotation (Faraday 1846; Stix 1992) are at play (Gueroult, Rax & Fisch 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable advance was introduced in 2011 when the rotary polarization drag was enhanced by about four orders of magnitude by using near-resonant slow-light in a rotating solid ruby rod [10]. Recently it was shown that the rotary polarization drag takes place on astronomical scale in the magnetosphere of rotating pulsars, offering a unique means to determine the rotation direction of pulsars [11]. The effect is especially important since it is nonreciprocal, i. e., creates asymmetric wave transmission between two locations.Here we propose an alternative system for creating rotational polarization drag at unprecedentedly 1 high specific rotation level -four orders of magnitude higher than in the above record slow-light experiment [10], and correspondingly -almost ten orders of magnitude higher than in the original Jones' observation [9].…”
mentioning
confidence: 99%
“…A remarkable advance was introduced in 2011 when the rotary polarization drag was enhanced by about four orders of magnitude by using near-resonant slow-light in a rotating solid ruby rod [10]. Recently it was shown that the rotary polarization drag takes place on astronomical scale in the magnetosphere of rotating pulsars, offering a unique means to determine the rotation direction of pulsars [11]. The effect is especially important since it is nonreciprocal, i. e., creates asymmetric wave transmission between two locations.…”
mentioning
confidence: 99%